2019
DOI: 10.1084/jem.20190738
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of low-affinity memory CD8+ T cells by corticosteroids

Abstract: Patients treated with immune checkpoint blockade (ICB) sometimes experience immune-related adverse events (irAEs), requiring immuno-suppressive drugs such as corticosteroids despite the possibility that immunosuppression may impair the antitumor effects of ICB. Here, we address the dilemma of using corticosteroids for the treatment of irAEs induced by ICB. ICB augments neoantigen-specific CD8+ T cell responses, resulting in tumor regression. In our model, simultaneous, but not late, administration of corticost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 41 publications
6
79
0
Order By: Relevance
“…A subgroup analysis according to irAE type or severity suggested that only cutaneous or endocrine irAEs as well as mild irAEs (grade 1 or 2) can be associated with better treatment outcomes. This was possibly due to the unnecessity for permanent discontinuation of ICI treatment [7] or for high-dose systemic glucocorticoid treatment, which can counteract antitumor immunity induced by ICI therapy [8]. These findings require a further clinical examination for verification, however.…”
Section: Positive Association Of Iraes With Ici Treatment Efficacymentioning
confidence: 99%
“…A subgroup analysis according to irAE type or severity suggested that only cutaneous or endocrine irAEs as well as mild irAEs (grade 1 or 2) can be associated with better treatment outcomes. This was possibly due to the unnecessity for permanent discontinuation of ICI treatment [7] or for high-dose systemic glucocorticoid treatment, which can counteract antitumor immunity induced by ICI therapy [8]. These findings require a further clinical examination for verification, however.…”
Section: Positive Association Of Iraes With Ici Treatment Efficacymentioning
confidence: 99%
“…Further, another recent study showed that low-affinity memory T cells are inhibited by corticosterone and that overall survival (OS) was reduced in melanoma patients who received corticosteroids along with ICB (Tokunaga et al, 2019). These observations highlight the need to understand the effects of low-versus high-dose administration of exogenous glucocorticoids and how these relate to the effects of endogenous glucocorticoid.…”
Section: Discussionmentioning
confidence: 97%
“…A recent paper also reported that simultaneous, but not delayed administration of corticosteroids impaired neo-antigen specific anti-tumor responses augmented by checkpoint blockade. 15 Reduced CD8 + T-cell proliferation and lack of protection upon rechallenge with tumors lacking the neoantigen were observed. Here, corticosteroids were shown to decrease low-but not high-affinity memory T cells by suppressing fatty acid metabolism essential for memory T cells.…”
Section: Discussionmentioning
confidence: 98%
“…A limited set of data indicates that Dexa administration is associated with poorer outcome of cancer patients in general [9][10][11][12] and that it specifically interferes with immune-checkpoint blockade as well as chemotherapy. [13][14][15][16] We are developing cancer vaccines which are based on tumor-antigen encoding RNA. Being a natural TLR7/8 ligand, RNA has intrinsic adjuvant activity and the antigen is delivered in an HLA-independent manner.…”
Section: Introductionmentioning
confidence: 99%